?Studies on the Fixed Oil of the Seed of Albizia Amara (Biological Sciences - PJSIR, 1995)
The free fatty acids were liberated from the oil and their methyl esters were prepared by standard procedures [11]. These esters were analysed using a Shimadzu GC-14A Gas Chromatograph equipped with a flame ionization detector and a packed glass column (1.6 m x 3 mm i.d.) containing